2005
DOI: 10.1126/science.1117004
|View full text |Cite
|
Sign up to set email alerts
|

Selection on Heritable Phenotypic Plasticity in a Wild Bird Population

Abstract: Theoretical and laboratory research suggests that phenotypic plasticity can evolve under selection. However, evidence for its evolutionary potential from the wild is lacking. We present evidence from a Dutch population of great tits (Parus major) for variation in individual plasticity in the timing of reproduction, and we show that this variation is heritable. Selection favoring highly plastic individuals has intensified over a 32-year period. This temporal trend is concurrent with climate change causing a mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
698
8
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 607 publications
(728 citation statements)
references
References 21 publications
18
698
8
4
Order By: Relevance
“…Together with the binary nature of our measure, this means that we could not easily explore innovation plasticity within individuals using a reaction norm approach [124,131 -134]. Such an approach might allow for G Â E and non-constant additive genetic variation to be detected and characterized [3].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Together with the binary nature of our measure, this means that we could not easily explore innovation plasticity within individuals using a reaction norm approach [124,131 -134]. Such an approach might allow for G Â E and non-constant additive genetic variation to be detected and characterized [3].…”
Section: Resultsmentioning
confidence: 99%
“…The great tit (Parus major) is a small iteroparous, socially monogamous and sexually dimorphic songbird, and for decades has been an influential model organism in many different areas of research including life-history variation [66], optimal foraging [67], phenotypic plasticity [3,68], evolutionary dynamics [69] and personality [44,70]. Strong selection on timing reproduction to coincide with peak caterpillar abundance has also made the great tit an important model species for the study of the phenology of trophic interactions [71].…”
Section: (A) the Study Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has shown that individual birds are remarkably flexible in their timing of breeding in a changing climate, allowing them to closely track changes in the environment [12][13][14]. This plasticity represents the ability of a single genotype to alter its phenotype in response to changing environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Variation in quality can have environmental (McNamara, 1998) or genetic (Nussey, Postma, Gienapp, & Visser, 2005) origins. For example, individuals who experience favorable environmental conditions early in life, known as “silver spoon” effects, can have reduced costs of reproduction throughout their lives (Vetter et al., 2016).…”
Section: Introductionmentioning
confidence: 99%